2010
DOI: 10.1097/tp.0b013e3181d2bff4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Organ Donation After Cardiac Death: Potential Donors in the Emergency Department

Abstract: BACKGROUND.: The continuing shortfall of organs for transplantation has increased the use of donation after cardiac death (DCD). We hypothesized that some patients who undergo tracheal intubation in the emergency department (ED) and who are assessed for, but not admitted to, critical care might have potential for controlled DCD. METHODS.: We identified all patients who underwent tracheal intubation in the ED between 2004 and 2008 and studied their records to identify those not admitted to an intensive care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…There were six death reviews that screened for potential donation after circulatory determination of death donors, using pre-specified criteria; however, the criteria varied between studies. 11,25,[31][32][33][34] Three death reviews investigated potential controlled donation after circulatory determination of death donors hospital-wide and found that 2.3%-3.6% died in the ED. 11,31,32 Similarly, two death reviews investigated potential uncontrolled donation after circulatory determination of death donors hospital-wide and found that 67%-75% died in the ED.…”
Section: Donation After Circulatory Determination Of Deathmentioning
confidence: 99%
“…There were six death reviews that screened for potential donation after circulatory determination of death donors, using pre-specified criteria; however, the criteria varied between studies. 11,25,[31][32][33][34] Three death reviews investigated potential controlled donation after circulatory determination of death donors hospital-wide and found that 2.3%-3.6% died in the ED. 11,31,32 Similarly, two death reviews investigated potential uncontrolled donation after circulatory determination of death donors hospital-wide and found that 67%-75% died in the ED.…”
Section: Donation After Circulatory Determination Of Deathmentioning
confidence: 99%
“…-Younger than 70, in alignment with methods used in past Canadian 15 and international studies; 39,40 and -Younger than 80, to reflect evolving practice and growing acceptance of older donors. 6 Factors Associated With Conversion A hierarchical logistic regression (main fixed effects model without random effects) was used to determine factors associated with becoming an organ donor.…”
Section: Appendix 1: Estimating Donor Potentialmentioning
confidence: 99%
“…Over a 5-year period in an ED averaging 100,000 visits a year, they found only 49 patients who had terminal withdrawal of life support, only 14 of whom would have been eligible for DCD. 4 Several other locales have developed out-of-hospital arrest DCD protocols. A recent pilot project in New York City yielded no donors after a 6-month trial period.…”
Section: Experiences With Dcd Involving the Ed And Emsmentioning
confidence: 99%
“…Emergency physicians may be called upon to participate in a hospital's controlled DCD protocol with very ill patients in the ED 4 and thus need to be familiar with controlled DCD. However, the most likely scenario in which EPs would become involved in DCD is through uncontrolled DCD, either with patients who are brought in from the field under such a protocol or with patients who fail ED resuscitation.…”
Section: Ethical Concerns Regarding Dcds Specific To the Edmentioning
confidence: 99%
See 1 more Smart Citation